Association of physical activity with risk of chronic kidney disease in China: A population-based cohort study - Shi, Kexiang; Zhu, Yunqing; Lv, Jun; Sun, Dianjianyi; Pei, Pei; Du, Huaidong; Chen, Yiping; Yang, Ling; Han, Bing; Stevens, Rebecca; Chen, Junshi; Chen, Zhengming; et al. (Journal of sport and health science, 2024)
•Total physical activity was inversely associated with the risk of chronic kidney disease (CKD).•Nonoccupational physical activity was inversely associated with the risk of CKD.•Both low-intensity and moderate- to vigorous-intensity physical activity were inversely associated with the risk of CKD.•Physical activity could be a target for intervention in CKD, no matter what type or intensity. Information on the association between physical activity (PA) and the risk of chronic kidney disease (CKD) is limited. We aimed to explore the associations of total, domain-specific, and intensity-specific PA with CKD and its subtypes in China. The study included 475,376 adults from the China Kadoorie Biobank aged 30–79 years during 2004–2008 at baseline. An interviewer-administered questionnaire was used to collect the information about PA, which was quantified as metabolic equivalent of task hours per day (MET-h/day) and categorized into 4 groups based on quartiles. Cox regression was used to analyze the association between PA and CKD risk. During a median follow-up of 12.1 years, 5415 incident CKD cases were documented, including 1159 incident diabetic kidney disease (DKD) cases and 362 incident hypertensive nephropathy (HTN) cases. Total PA was inversely associated with CKD risk, with an adjusted hazard ratio (HR, 95% confidence interval (95%CI)) of 0.83 (0.75–0.92) for incident CKD in the highest quartile of total PA as compared with participants in the lowest quartile. Similar results were observed for risk of DKD and HTN, and the corresponding HRs (95%CIs) were 0.75 (0.58–0.97) for DKD risk and 0.56 (0.37–0.85) for HTN risk. Increased nonoccupational PA, low-intensity PA, and moderate-to-vigorous-intensity PA were significantly associated with a decreased risk of CKD, with HRs (95%CIs) of 0.80 (0.73–0.88), 0.85 (0.77–0.94), and 0.85 (0.76–0.95) in the highest quartile, respectively. PA, including nonoccupational PA, low-intensity PA, and moderate-to-vigorous-intensity PA, was inversely associated with the risk of CKD, including DKD, HTN, and other CKD, and such associations were dose dependent. [Display omitted]